Synthesis and characterization of new redox-active polymers based on 10-(1, 3-dithiol-2-ylidene)anthracen-9(10H)-one derivatives. (26th June 2015) - Schmidt, Daniel; Häupler, Bernhard; Friebe, Christian; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Redox-active materials based on a 10-(1, 3-dithiol-2-ylidene)anthracen-9(10 H )one core were synthesized by the introduction of a polymerizable vinyl group in 3-position, resulting in a redox-active monomer, which possess both electron donating and electron accepting properties. The electron accepting properties can be tailored by straightforward one-step modifications of the carbonyl functionality to N -cyanoimine, dicyanomethylene or thione moieties, respectively, leading to bipolar compounds. These monomers can be polymerized by free radical polymerization. The resulting polymers could be obtained with molar masses of 6, 500 to 24, 300 g/mol as well as yields of up to 92% and were examined with 1 H NMR and SEC. Their electrochemical behavior reveals reversible reductions comparable with the redox properties of the corresponding monomers. After further optimization, these materials could become potentially interesting for applications in organic batteries. Graphical abstract: New redox-active polymers consisting of 10-(1, 3-dithiol-2-ylidene)anthracen-9(10 H )-one derivatives were synthesized and their electrochemical properties were examined by cyclic voltammetry. The monomers as well as the polymers showed stable redox potentials and are potential candidates for organic electronics applications like organic radical batteries. Highlights: Four new redox-active compounds based on a 10-(1, 3-dithiol-2-ylidene)anthracen-9(10 H )one core were synthesized. The electron accepting properties could be tailored by straightforward one-step reactions. All monomers could be polymerized by free radical polymerization. The monomers reveal reversible oxidations and reductions. The polymers show irreversible redox processes.